(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Prevention is especially critical for cardiovascular diseases and electrocardiogram (ECG) is the most undisputed and widely accepted tool to detect and diagnose them. Apart from their enormous impact in older people life expectancy, cardiovascular diseases are also the main cause of death for the population among 44 and 64 years and detecting their symptoms in time is critical to avoid irreparable damages or death. Never the-less, methods and systems to acquire an ECG signal with good enough quality in a fast and easy-to-use manner, so that they can be used in domestic or other non-clinical environments, are nowadays far from common. This is mainly because traditional ECG acquisition systems usually require the use of several cables and electrodes attached to the body, sometimes with conducting gel to increase the contact, making them embarrassing and difficult to use.